2020
DOI: 10.1128/mra.00905-19
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Rhodococcus ruber R1, a Novel Strain Showing a Broad Catabolic Potential toward Lignin-Derived Aromatics

Abstract: Rhodococcus ruber R1 was isolated from a pulp mill wastewater treatment plant because of its ability to use methoxylated aromatics as growth substrates. We report the 5.56-Mb genome sequence of strain R1, which can provide insights into the biodegradation of lignin-derived phenolic monomers and potentially support processes for lignocellulose conversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Results showed that Rhodococcus strains harboring vanAB -like genes similar to R. ruber R1 as R. ruber DSM 43338 T , R. ruber Chol-4 and R. pyridinivorans JCM 10940 T [ 8 , 44 , 45 ], and vanAB genes comparable to R. jostii RHA1 as R. aetherivorans BCP1 [ 46 , 47 ] were able to grow on VA and its O-demethylation product, PCA ( Figure 4 ), suggesting that all these strains contain proficient VanOD-encoded genes and a functional PCA pathway ( Figure 1 D). We also included in our growth profile assays marine-isolated Rhodococcus strains MS13 and H-CA8f as control [ 48 , 49 ], since they apparently do not harbor VanOD-encoded genes, even though they carry the classical PCA pathway [ 50 ], as revealed by BLAST searches and confirmed by growth on PCA as a sole carbon and energy source ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that Rhodococcus strains harboring vanAB -like genes similar to R. ruber R1 as R. ruber DSM 43338 T , R. ruber Chol-4 and R. pyridinivorans JCM 10940 T [ 8 , 44 , 45 ], and vanAB genes comparable to R. jostii RHA1 as R. aetherivorans BCP1 [ 46 , 47 ] were able to grow on VA and its O-demethylation product, PCA ( Figure 4 ), suggesting that all these strains contain proficient VanOD-encoded genes and a functional PCA pathway ( Figure 1 D). We also included in our growth profile assays marine-isolated Rhodococcus strains MS13 and H-CA8f as control [ 48 , 49 ], since they apparently do not harbor VanOD-encoded genes, even though they carry the classical PCA pathway [ 50 ], as revealed by BLAST searches and confirmed by growth on PCA as a sole carbon and energy source ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we isolated a bacterial strain belonging to the Rhodococcus genus from a pulp mill wastewater treatment plant identified as Rhodococcus ruber strain R1, whose genome sequence consisted of one chromosome (~5.3 Mbp) and two plasmids (~179 and ~33 kbp), revealing an extensive catabolic potential [ 8 ]. Strain R1 has the ability to grow on various lignin-derived phenolic monomers, including p -coumarate and 4-hydroxybenzoate [ 8 ], which are typically catabolized via β-ketoadipate through the ring-cleavage intermediate protocatechuate (PCA) in Rhodococcus species [ 9 , 10 ]. Accordingly, we have currently confirmed that strain R1 is capable to grow on vanillate (VA), an additional lignin-derived product generated from the metabolism of ferulate and vanillin [ 10 , 11 ], as a sole carbon and energy source.…”
Section: Introductionmentioning
confidence: 99%
“…Biodegration of lignin can be observed in nature with enzymes produced by different fungal species and bacterial species [9,10]. Even though, the lignin cannot be digested by cattle and therefore is not suitable for use in animal husbandry as a feed source.…”
Section: Introductionmentioning
confidence: 99%